Current Sensors for Monitoring and Protecting Devices in the Alternating Current Traction Power Network - Amirov S. F.; Norjigitov S. A.; Karimov I. A. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The reliable operation of AC traction power networks is increasingly critical as electrified railway lines expand. Specific Background: Existing monitoring systems in Uzbekistan rely solely on measurements at substations, leaving long contact networks unmonitored and vulnerable to voltage loss and interphase short circuits, especially in neutral sections. Knowledge Gap: Current protection methods only respond after an electric arc forms, lacking proactive detection and prevention mechanisms. Aims: This study aims to design and test an autonomous current sensor capable of real-time current monitoring and early detection of abnormal conditions to prevent arc formation in neutral sections. Results: A functional sensor prototype was developed using a microcontroller-based design that converts catenary current to a unipolar signal, calculates root mean square (RMS) values, and transmits data wirelessly via ESP-NOW. Field tests on an operating traction network demonstrated reliable current measurement but revealed limitations in wireless communication reliability and solar-powered autonomy. Novelty: The system integrates low-cost components, high-accuracy analog-to-digital conversion, and autonomous solar power with proactive disconnection capabilities, representing a new approach to early fault prevention in traction networks. Implications: With improvements in communication and power supply, the proposed sensor offers a scalable solution for enhancing safety and operational efficiency in modern railway electrification systems. Highlights: Early detection of interphase short circuits Low-cost, autonomous sensor with solar power Real-time wireless current monitoring Keywords: Current Sensor, Traction Network, Microcontroller, Wireless Monitoring, AC Railway